2017
DOI: 10.1042/cs20170218
|View full text |Cite
|
Sign up to set email alerts
|

miR-223 represents a biomarker in acute and chronic liver injury

Abstract: miR-223 represents a promising diagnostic marker in a panel of serum markers of liver injury. Together with previously published data, our results highlight that the role of miR-223 in the pathophysiology of the liver is complex and needs further analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…However, a recent study suggests that miR‐223 does not play a role in controlling acute liver injury in several mouse models and in controlling liver fibrosis induced by chronic CCl 4 treatment . Part of the reason for the discrepancy between that study’s results and ours may be the different wild‐type (WT) control mice used (WT littermate control mice were used in our study but not in the other study). Interestingly, several recent studies have reported that levels of miR‐223 were up‐regulated in the liver in a mouse model of NASH and elevated in the serum in NASH patients .…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…However, a recent study suggests that miR‐223 does not play a role in controlling acute liver injury in several mouse models and in controlling liver fibrosis induced by chronic CCl 4 treatment . Part of the reason for the discrepancy between that study’s results and ours may be the different wild‐type (WT) control mice used (WT littermate control mice were used in our study but not in the other study). Interestingly, several recent studies have reported that levels of miR‐223 were up‐regulated in the liver in a mouse model of NASH and elevated in the serum in NASH patients .…”
contrasting
confidence: 57%
“…We have previously demonstrated that miR‐223 plays an important role in attenuating alcoholic liver injury and acetaminophen‐induced liver injury by targeting interleukin‐6 ( Il6 ) and inhibitor of nuclear factor kappa B (NF‐κB) kinase subunit alpha genes in neutrophils . However, a recent study suggests that miR‐223 does not play a role in controlling acute liver injury in several mouse models and in controlling liver fibrosis induced by chronic CCl 4 treatment . Part of the reason for the discrepancy between that study’s results and ours may be the different wild‐type (WT) control mice used (WT littermate control mice were used in our study but not in the other study).…”
mentioning
confidence: 56%
“…Asterisks indicate whether there were significant differences among the groups. *P < 0.05; **P < 0.01. www.nature.com/scientificreports www.nature.com/scientificreports/ was detected; (iii) and previously published data regarding the miRNAs profile in decompensated cirrhosis 17,18 , inflammation 19,20 , and sepsis [21][22][23] .…”
Section: Discussionmentioning
confidence: 78%
“…Based on the magnitude of expression difference between patients with and without ACLF in the microarray analysis and in literature reports [17][18][19][20][21][22][23] miRNAs miR-106b-5p, miR-126-3p, miR-20a-5p, miR-223-3p, and miR-25-3p were selected to be further validated by RT-qPCR. Some miRNAs that had high FC values such as let-7a-5p and let-7g-5p were not detected in most microarray samples and were therefore not included in the validation step.…”
Section: Resultsmentioning
confidence: 99%
“…In acute and chronic liver injury models, hepatic miR-223 up-regulation was restricted to hepatocytes, and correlated with the degree of liver injury and hepatic cell death. Moreover, elevated miR-223 expression was significantly higher in the serum, following acute liver injury [36].…”
Section: Micrornasmentioning
confidence: 92%